Variants of Psychopathy in Chinese Juvenile Offenders: A Latent Profile Analysis - Wang, Meng-Cheng (Criminal justice and behavior, 2022)
Despite considerable understanding on the psychopathy subtypes in detained populations, the variants of psychopathy in non-Western populations are less well understood. To address this gap, the present study conducted a series of latent profile analyses with the factors of the Youth Psychopathic Traits Inventory, childhood trauma, and trait anxiety in 560 Chinese incarcerated boys (Mage = 16.92, SD = 0.81). Four subgroups emerged: relatively normal (67.3%); callous, psychopathy-like (2.8%); moderate psychopathy-like (24.8%); and high traumatic, moderate psychopathy-like (5.1%). Moreover, the modified Bolck–Croon–Hagenaars method was used to examine the significant mean differences on covariates across profiles, including proactive aggression, reactive aggression, affective empathy, and cognitive empathy. Results showed that the psychopathic profiles displayed differences on key variables. The callous, psychopathy-like group endorsed higher aggression and lower empathy. This study provides initial empirical support for the existence of psychopathy variants and enhances the understanding of the psychopathic construct in non-Western cultures.